2008
DOI: 10.1093/ejo/cjn030
|View full text |Cite
|
Sign up to set email alerts
|

Tooth size discrepancies among Jordanian schoolchildren

Abstract: The aims of this study were to determine the tooth size discrepancies (TSD) in a representative sample of Jordanian schoolchildren and to compare TSD between genders. Dental casts of 367 (174 males and 193 females; mean age 15.5 years) Jordanian schoolchildren were selected. Anterior and overall Bolton ratios were determined using a digital calliper. Differences between genders were analyzed using a t-test. The results showed that there were no significant differences in the TSD between males and females. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
11
2
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 15 publications
3
11
2
1
Order By: Relevance
“…This difference was also observed in the cumulative tooth size widths, where males exceeded those of the females by 2.04 mm in the maxilla and 2.22 mm in the mandible [Table 3]. This finding is in agreement with those reported for other Arabian groups of Iraqis,[5] Jordanians,[71315] and Saudis,[12] and also for other racial groups. [41114]…”
Section: Discussionsupporting
confidence: 88%
See 4 more Smart Citations
“…This difference was also observed in the cumulative tooth size widths, where males exceeded those of the females by 2.04 mm in the maxilla and 2.22 mm in the mandible [Table 3]. This finding is in agreement with those reported for other Arabian groups of Iraqis,[5] Jordanians,[71315] and Saudis,[12] and also for other racial groups. [41114]…”
Section: Discussionsupporting
confidence: 88%
“…Al-Khateeb and Abu Alhaija[13] and Al-Omari et al .,[15] in their studies on Jordanians’ dentition, reported anterior and overall ratios that were very close to Bolton's ratios. Further, Al-Tamimi and Hashim[16] carried out a study on Saudi population and found that the anterior and overall ratios were very similar to Bolton's values.…”
Section: Introductionmentioning
confidence: 80%
See 3 more Smart Citations